Dampak Code-Switching terhadap Perolehan Bahasa Inggris: Perspektif Sosiolinguistik - Mariana Mariana; Rudi Purwana (Pusat Riset dan Inovasi Nasional, 2022)
Code-switching, a phenomenon in which speakers alternate between two or more languages within a conversation, has garnered attention in the field of linguistics, particularly in the context of language acquisition. In the English language context, code-switching practices are becoming increasingly common, especially in multilingual communities worldwide. This study aims to investigate the impact of code-switching on the acquisition of English language, focusing on a sociolinguistic perspective. The sociolinguistic approach allows for a better understanding of the social and cultural contexts in which code-switching occurs, as well as its effects on language learning. This research utilizes a qualitative approach by analyzing data from interviews and observations within multilingual communities. Findings indicate that code-switching can influence various aspects of language acquisition, including vocabulary mastery, sentence structure, and pragmatic understanding. Additionally, code-switching practices can enrich language learning experiences by introducing speakers to language variations and different social contexts. The findings of this study provide valuable insights for language education practitioners and learners to comprehend the phenomenon of code-switching in the context of English language acquisition.